CORRELATION OF HUSBAND'S KNOWLEDGE AND SUPPORT TO IVA TEST BEHAVIOR IN WOMEN OF FERTILE AGE COUPLES IN NAMORAMBE VILLAGE, NAMORAMBE SUB DISTRICT IN 2017 - Hanna Sriyanti Saragih; Julietta Hutabarat (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2019)
One of the cervical cancer screening can be done with visual inspection of acetic acid (IVA Test). InIndonesia, almost 70% of cervical cancers were found in advanced stages (> stage II B). This is due to thelow level of screening, which was <5% where ideally was 80%. This research is to find out the correlationbetween husband's knowledge and support to IVA test behavior in women of fertiled age couples. This typeof research was analytic descriptive with cross sectional design carried out in Namorambe Village,Namorambe sub district. The population used in the study were all women of fertiled age who live inNamorambe village. Samples were taken by simple random sampling of 58 respondents. Data collectionusing questionnaires and data analyzed univariate and bivariate using Fisher Exact statistical tests. Theresults of statistical analysis showed that knowledge’s level of the respondents was mostly in less category of24 people (41.4%), husband's support for IVA test behavior was at less category of 39 people (67.2%), themost respondents did not do IVA test of 45 people (77.6 %). In bivariate analysis, with p-value of 0.001<0.05, it was concluded that there was significant correlation between knowledge with IVA examinationbehavior, and with a p-value of 0.04 <0.05. It was concluded that there was correlation between husband'ssupport and IVA examination behavior. It was need to increase knowledge about cervical cancer and IVAtest through education by health workers through the promotion of reproductive health.